Baby's best Foe-riend: Endogenous retroviruses and the evolution of eutherian reproduction. (15th September 2021) - Zhang, Xuzhe; Muglia, Louis J.
Abstract: High maternal investment in pregnancy and the perinatal period are prominent features of eutherian reproduction. Viviparity increases offspring survival, favoring high maternal prenatal investment. Matrotrophy through the placenta reduces maternal investment at early pregnancy, allowing the mother to abort embryos of subpar quality, therefore reducing resources wastage. On the other hand, intimate maternal-fetal interplay enables the fetus to manipulate maternal physiology to acquire more resources. This parent-offspring conflict likely drives the evolution of eutherian placentation, which is facilitated by the endogenous retroviruses (ERVs), ancient retroviruses that invaded host genome millions of years ago. ERVs bring new genes and novel regulatory elements into host genome, contribute to maternal-fetal tolerance, placenta-specific cell type formation, trophoblast gene expression network rewiring, and the establishment of imprinting. However, retroviruses/ERVs can function as infectious pathogens that interfere with host immune and inflammation pathways and cause genomic instability. In addition, ERVs coopted for host function may contribute to pathogenesis during infections due to their susceptibility to mechanisms activated by the invading pathogens. ERVs have been implicated in multiple perinatal adverse outcomes, therefore, eutherians must have evolved control mechanisms to regulate their function. Here we propose the TRIM family as an important participant of host antiviral defense and a likely candidate that mediates the coevolution of ERVs and their eutherian host. TRIMs have been shown to interact with retroviruses during each step of the infectious cycle. Understanding TRIMs' role in ERV regulation in the placenta may provide insight to both the physiology and pathology of eutherian reproduction. Highlights: High maternal investment and parent-offspring conflict drive placenta evolution. ERVs bring in genetic novelties, facilitating eutherian placentation evolution. ERVs may harm eutherian reproduction due to their viral background. TRIMs regulate each step of retroviral/ERV infectious cycle.